2002
DOI: 10.1159/000051827
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Features of Pemphigus vulgaris in Patients with Bullous Pemphigoid

Abstract: Background: The simultaneous presence of features of pemphigus vulgaris (PV) in patients with bullous pemphigoid (BP) has previously been reported in the literature. Objective: The purpose of this retrospective study is to present 13 patients with an initial diagnosis of BP, who subsequently demonstrated coexistent serological features of both BP and PV. Methods: The following information on each patient was documented, at the time of initial diagnosis: clinical profile on presentation, histology, direct immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
(104 reference statements)
1
16
2
Order By: Relevance
“…Subsequent studies in larger groups of patients, however, have shown that PF patients occasionally have Abs to Dsg3 as well, 1,7 and that not all PV and PF patients have Abs to Dsg1 and/or Dsg3 3,5,8 . Furthermore, anti‐Dsg Abs have been occasionally demonstrated in normal controls, and in patients with other bullous diseases, including bullous pemphigoid 1,5,9 . Some investigators have found that a significant minority of patients do not have the PV phenotype predicted by their Dsg autoantibody profile 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies in larger groups of patients, however, have shown that PF patients occasionally have Abs to Dsg3 as well, 1,7 and that not all PV and PF patients have Abs to Dsg1 and/or Dsg3 3,5,8 . Furthermore, anti‐Dsg Abs have been occasionally demonstrated in normal controls, and in patients with other bullous diseases, including bullous pemphigoid 1,5,9 . Some investigators have found that a significant minority of patients do not have the PV phenotype predicted by their Dsg autoantibody profile 8 …”
Section: Introductionmentioning
confidence: 99%
“…3,5,8 Furthermore, anti-Dsg Abs have been occasionally demonstrated in normal controls, and in patients with other bullous diseases, including bullous pemphigoid. 1,5,9 Some investigators have found that a significant minority of patients do not have the PV phenotype predicted by their Dsg autoantibody profile. 8 Despite the commercial availability of ELISAs to detect anti-Dsg1 and anti-Dsg3 Abs, most laboratories still rely on IIF techniques to detect pemphigus autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 patient had BP appearing 15 years after the onset of PV, however, the patient had anti‐ICS antibodies before, during and after the onset of BP. In the 17 patients with concomitant BP and PV, 70% had cutaneous confined disease, implying a lack of mucosal disease 14 . Ninomiya et al described a patient with BP and PV that was confirmed by DIF and IIF, and on immunoblot was found to be reactive to a 190‐kD protein, possibly implying PNP.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG lowers antibody titers to dsg 1 and dsg 3, often making them undetectable. [235][236][237][238][239][240] IVIG has been shown to be effective in the treatment of PV in numerous studies as summarized in Table XVI. In the two largest studies, which are from one institution, 42 patients were treated with IVIG (2 g/kg every 4 weeks) until control was achieved, as defined by healing of old lesions and no new lesions.…”
Section: Autoimmune Bullous Diseasesmentioning
confidence: 99%